Narcolepsy Following Yellow Fever Vaccination: A Case Report - Rosch, Richard E.; Farquhar, Michael; Gringras, Paul; Pal, Deb K. (Frontiers in Neurology, 2016)
Narcolepsy with cataplexy is a rare, but important differential diagnosis for daytime sleepiness and atonic paroxysms in an adolescent. A recent increase in incidence in the pediatric age group probably linked to the use of the Pandemrix influenza vaccine in 2009, has increased awareness that different environmental factors can “trigger” narcolepsy with cataplexy in a genetically susceptible population. Here, we describe the case of a 13-year-old boy with narcolepsy following yellow fever vaccination. He carries the HLA DQB1*0602 haplotype strongly associated with narcolepsy and cataplexy. Polysomnography showed rapid sleep onset with rapid eye movement (REM) latency of 47 min, significant sleep fragmentation and a mean sleep latency of 1.6 min with sleep onset REM in four out of four nap periods. Together with the clinical history, these findings are diagnostic of narcolepsy type 1. The envelope protein E of the yellow fever vaccine strain 17D has significant amino acid sequence overlap with both hypocretin and the hypocretin receptor 2 receptors in protein regions that are predicted to act as epitopes for antibody production. These findings raise the question whether the yellow fever vaccine strain may, through a potential molecular mimicry mechanism, be another infectious trigger for this neuro-immunological disorder.